"Are you feeling what I'm feeling?": an analysis of communication and emotional work of Korean social workers - Kim, Min Kyung, author; Williams, Elizabeth A., advisor; Long, Ziyu, committee member; Timpson, William, committee member (Colorado State University. Libraries, 2016)
This study investigates how Korean social workers experience and communicate emotional work in their organizational experience. Using a qualitative interview approach, I explore the emotional experiences of Korean social workers. Korean social workers experience wide array of different types of emotional work, however, expresses them implicitly and indirectly due to contemplative and considerate communication tactics in order to save others’ face and avoid burdening others with their emotions. Furthermore, the emotional work experience leads Korean social workers to develop a sense of pride, responsibility, and compassion toward their clients which were not inherent from the beginning of their professional experience due to lack of autonomy when choosing their profession. Korean social workers also communicate their emotional work through in-group association, strongly relying on connections through their alma mater, others who are their age, their position, and their tenure in the organization. However, a notable challenge to the original theory of emotional work is that for Korean social workers they also experience emotional labor and emotional dissonance due to organizational constraints that generate a clash of inner feeling with what organizations expect them to present. The study provides evidence of how different cultural expectations influence emotional work experiences as well as the communication of emotion. The findings not only support the different cultural norms and constraints that influence Korean social workers’ emotional work but also contribute to further the understanding of the role of organizations in providing proper outlets for emotional work experiences.
Are you feeling what I'm feeling?: an analysis of communication and emotional work of Korean social workers
Keywords: emotional work; organizational communication; communication; social workers; Korea